Hubungan Tekanan Darah Terhadap Daya Tahan Kardiovaskular Pada Atlet Kempo di Kabupaten Buleleng - Luh Ita Mahendrayani; Hendra Mashuri; Hesteria Friska Armynia Subratha (Undiksha Press, 2026)
This study aims to determine the relationship between blood pressure and cardiovascular endurance in kempo athletes in Buleleng district. The research method used was a cross-sectional study with analysis of the results of blood pressure measurements using a sphymomanometer and cardiovascular endurance using the MFT (Multistage Fitness Test. The research results from the chi square test obtained a p value of 0.016 (p<0.05, rejecting Ho and accepting H1), so it can be concluded that there is a significant relationship between blood pressure and VO2Max. Where there is a clear tendency for athletes with normal blood pressure to tend to have better VO2Max than athletes who have blood pressure that is classified as pre-hypertension, because athletes with blood pressure Those who are classified as pre-hypertensive tend to have VO2Max which is classified as low to very low. The conclusion from this study is that blood pressure in athletes is more in the pre-hypertension category (60%) in adolescence, while cardiovascular endurance or VO2max in athletes is more in the category less (33%). This study there is a relationship between blood pressure which affects cardiovascular endurance in kempo athletes. Keywords: blood pressure; cardiovascular endurance; kempo